Impact of China’s National Volume-Based Procurement policy exclusively for insulin on the volume, expenditure and price: an interrupted time series analysis in Guangdong Province - Jiang, Changsong; Nie, Manling; Lu, Yun; Jiang, Ting; Guo, Dan; Qi, Peng; Li, Na; Chang, Feng (Frontiers in Public Health, 2025)
ObjectiveThis study aims to evaluate the effect of China’s National Volume-Based Procurement (NVBP) policy exclusively for insulin by analyzing the trend in volume, expenditure, and price before and after NVBP policy.MethodsTaking Guangdong Province, China as an example, descriptive statistics and interrupted time series analysis were used to quantitatively measure the immediate and long-term effect of the NVBP policy on insulin volume, expenditure and price. In terms of volume, subgroup analysis is further conducted based on different generations and enterprise ownership to examine the impact of NVBP on the insulin utilization pattern.ResultsFollowing the implementation of the NVBP policy, monthly insulin procurement volume increased significantly from 7.69 million to 9.37 million defined daily doses (DDDs), while monthly expenditure decreased from CNY 86.64 million to CNY 52.55 million, accompanied by a reduction in defined daily dose cost (DDDc) from CNY 11.24 to CNY 5.57. Interrupted time series analysis (ITSA) confirmed these trends, showing an immediate post-intervention increase of 1.547 million DDDs (p < 0.001), expenditure reduction of CNY 42.57 million (p < 0.001), and DDDc decrease of CNY 5.427 (p < 0.001) in instantaneous level. Subgroup analysis demonstrated divergent trends between insulin generations, with non-significant decrease in second-generation insulin and increase in third-generation insulin procurement in long-term trend. Notably, domestic insulin showed a significant increase in procurement volume (p < 0.05), while imported insulin exhibited a non-significant declining trend.ConclusionThese findings demonstrate that the NVBP policy significantly reduced insulin expenditure while improving treatment accessibility and affordability for insulin. The policy effectively promoted therapeutic upgrading from human insulin to insulin analogue and optimized medication regimen. Notably, it stimulated domestic insulin market development through substitution effect. This multi-dimensional improvement exemplifies the principles of value-based healthcare delivery.